Sudden change in quantum and classical correlations and the unruh effect - Céleri, L. C.; Landulfo, A. G.S. [UNESP]; Serra, R. M.; Matsas, G. E.A. [UNESP] (American Physical Society (APS), 2010)
We use the Unruh effect to analyze the dynamics of classical and quantum correlations for a two-qubit system when one of them is uniformly accelerated for a finite amount of proper time. We show that the quantum correlation is completely destroyed in the limit of infinite acceleration, while the classical one remains nonzero. In particular, we show that such correlations exhibit the so-called sudden-change behavior as a function of acceleration. Eventually, we discuss how our results can be interpreted when the system lies in the vicinity of the event horizon of a Schwarzschild black hole. © 2010 The American Physical Society.